PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA TAHUN 2018-2021 - Poly Endrayanto Eko Christmawan; Rahmawati, Lisna Millah; Arisudhana, Aditya; Kussuma, Andre (Universitas Mercu Buana Yogyakarta, 2024)
This study examines the effect of profitability, company size, and leverage on tax avoidance in the mining company sector listed on the Indonesia Stock Exchange in 2018-2021. The independent variables in this study are profitability, firm size, and leverage, the dependent variable is tax avoidance. The type of research used is a quantitative method with secondary data derived from audited annual financial reports and obtained from www.idx.co.id. This study used a population of mining companies in 2018-2021. In taking the sample, a purposive sampling technique was used, with this technique a total of 44 samples were obtained from 11 companies with 4 years of observation. Then to determine the effect of each variable tested using multiple linear regression. The results of the study are that profitability as assessed by return on assets has a negative and significant effect on tax avoidance, company size as assessed by the natural logarithm of total assets has a positive and significant effect on tax avoidance, and leverage as assessed based on the debt to equity ratio has an influence positive and significant to tax avoidance. Implications of the research are: (a) Profitability. The higher the company's profit level, the less likely the company is to engage in tax avoidance, (b) Company Size. Large companies tend to utilize experts and asset depreciation to reduce tax payments, but must still comply with tax regulations so as not to harm stakeholders, (c) Leverage. Companies with debt tend to increase interest expenses to reduce tax expenses.